A brand to trust. - New Straits Times, (2011)
MALAYSIA will,according to the minister responsible for Islamic affairs,have the first government halal laboratory in the world.The Malaysian Halal Institute Analysis Laboratory (MHIAL),which will be built in Bandar Enstek,Negeri Sembilan,and ready by next year,will thus make the Department of Islamic Development Malaysia(JAKIM)the main reference point for halal certification in the country and,it is hoped,globally.After all,even without the MHIAL,Jakim,working with laboratories in Universiti Putra Malaysia,has already built a respectable foreign clientele. The proposed laboratory will reinforce Malaysia's already strong credentials as an international halal hub.